A Case Study of a Sport‐for‐Development Programme in Brazil. (28th December 2018) - Hall, Gareth; Reis, Arianne
Abstract : This article examines the 'Sport Works' narrative of sport‐for‐development practitioners of an inter‐organisational sport‐for‐development (SfD) programme utilising rugby to foster positive social transformation in Brazil. In doing so, we address an under‐representation of practitioners who are often seen as subjugated voices in SfD programmes. The paper also addresses an under‐representation of Brazil as a research site in SfD literature. Following several site visits and interviews with practitioners, our data concludes that despite a novel context of Brazil and the alternative values to football offered through the sport of rugby, practitioners and programme managers maintain dominant narratives of social transformation through sport without clear monitoring and evaluation.